2019
DOI: 10.1002/brb3.1447
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the unwanted: A systematic review of instruments used to assess negative effects of psychotherapy

Abstract: ObjectiveWhile the efficacy of psychotherapy in the treatment of mental disorders is well examined, systematic research into negative effects of psychotherapy seems comparatively rare. Therefore, this review evaluates instruments for assessing negative effects of psychotherapy in order to create a consensus framework and make recommendations for their assessment.MethodsThe study selection procedure follows current best‐practice guidelines for conducting systematic reviews, with 10 included studies in three dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 47 publications
0
55
0
1
Order By: Relevance
“…If participants skipped certain items of the INEP (e.g., about partnership), missing values were replaced with “0,” i.e., as if no NEP was present. Items in the INEP proved reliable; Cronbach’s α = 0.86 ( Ladwig et al, 2014 ; Herzog et al, 2019 ). In this investigation, Cronbach’s α values were 0.61 in study 1 and 0.87 in study 2.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…If participants skipped certain items of the INEP (e.g., about partnership), missing values were replaced with “0,” i.e., as if no NEP was present. Items in the INEP proved reliable; Cronbach’s α = 0.86 ( Ladwig et al, 2014 ; Herzog et al, 2019 ). In this investigation, Cronbach’s α values were 0.61 in study 1 and 0.87 in study 2.…”
Section: Methodsmentioning
confidence: 95%
“…However, many psychotherapists pay little attention to NEP in their own clinical practice and report to be unfamiliar with methods and criteria for identifying and preventing NEP ( Bystedt et al, 2014 ; Schermuly-Haupt et al, 2018 ). To enhance treatment outcome and patients’ wellbeing, the early identification of NEP and its conscious handling both in research and clinical practice is called for ( Meister et al, 2016 ; Herzog et al, 2019 ). As shown by the review of Jonsson et al (2014) , only 21% of randomized controlled trials of psychological treatments reported harm on the patient level.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present metasynthesis also highlight the importance of considering adverse effects of psychological therapies. These have historically been under-researched in the field and although there has been increasing recognition of the potential for and incidence of adverse effects, they remain under-assessed in clinical trials [64]. While it might be inevitable that some individuals experience therapy as challenging or even unhelpful, there are also findings that reveal the potential for harm, such as reports of finding other group members' emotions overwhelming; finding practicing certain techniques overwhelming; or finding that the Bodyscan can generate flashbacks.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this review published two decades ago, there remains limited development in methodologies to monitor such negative effects. A recent review of instruments to monitor negative effects found nine available instruments including one specifically for group psychotherapy published in German [64]. The authors found these measures to be inadequately validated and recommended that work was needed to develop a comprehensive consensus framework which could be used in routine outcome monitoring and research.…”
Section: Discussionmentioning
confidence: 99%
“…Statt der Messung der Therapieeffekte auf Skalenebene sollten (auch) die Item-und Personenebenen einschließlich der neuen Methoden zu symptomspezifischen Analysen einbezogen werden [5]. Schließlich gilt es, die jahrzehntelang in der Psychotherapie vernachlässigte Nebenwirkungsorientierung aufzugreifen, indem die negativen Effekte (Nebenwirkungen sowie unethisches Verhalten und Kunstfehler) im Prozess erfasst werden, um Psychotherapien nebenwirkungsärmer durchzuführen [33,42].…”
Section: Neue Outcome-maßeunclassified